Теоретико – методологічні основи оцінки трудового потенціалу підприємства - Нестеренко, Світлана Анатоліївна; Нестеренко, Светлана Анатольевна; Nesterenko, Svitlana (My University, 2017)
UK: В статті розглянуті теоретико методологічні особливості побудови алгоритму оцінки трудового потенціалу підприємства або галузі. Предметом дослідження є сукупність теоретичних і методологічних питань щодо визначення перспективної оцінки трудового потенціалу підприємств в умовах транзитивної економіки в Україні. EN: Objective need for further deepening of theoretical research and improvement of methodological approaches to the assessment of employment potential in order to improve processes of its formation and use determine the purpose and relevance of the research. Results. Update algorithm of labor (human resources) capable to based on these principles of integrated rehabilitation. Reproduction of labor (human) capacity as a determining element of social production is its constant movement in the production, distribution, exchange, consumption. The content of each phase is the processes which object is the labor force. Phase-by-phase reproduction of labor potential is linked to the conditions of reproduction of social and economic relations. Though, the structure, organizational-economic mechanism of reproduction of labor potential should be considered as an aggregated model – a system of 3 subsystems: phase formation, phase distribution and the phase of use of labor potential.
Theoretical and methodological basis of rating the labor potential of enterprise
Keywords: атрибутивні складові; релятивні складові; трудовий потенціал; відтворення ресурсів праця; активність; населення; зайнятість; стимулювання праці; синергія; attributive constituents; relational components; labor potential; reproduction of resources; activity; population; employment; labor stimulation; synergy